2006
DOI: 10.4103/0255-0857.19890
|View full text |Cite
|
Sign up to set email alerts
|

Detection of biofilm formation among the clinical isolates of Staphylococci: An evaluation of three different screening methods

Abstract: Purpose: The purpose of this study was to evaluate three methods for detection of biofilm formation in staphylococci. Methods: For detection of biofilm formation, 152 clinical isolates of Staphylococcus spp. were screened by tissue culture plate (TCP), Tube method (TM) and Congo red agar (CRA) method. Results: Of the 152 Staphylococcus spp. 88(57.8%) displayed a biofilm-positive phenotype under the optimized conditions in the TCP method and strains were further classified as high 22 (14.47 %) and moderate 60 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

57
424
7
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 466 publications
(515 citation statements)
references
References 19 publications
57
424
7
10
Order By: Relevance
“…In Hou's study, among 55.56% of isolates that produced biofilm in phenotypic test, 11.11% contained the icaA gene (26), but the other genes has not been investigated. In this study, methicillin resistant isolates harbored higher rate of icaADBC genes compared to MSSA, but no significant difference was confirmed, similar to two other studies (27,28). Moreover, Smith determined no significant relation between susceptibility to methicillin and biofilm formation (29).…”
Section: Discussionsupporting
confidence: 85%
“…In Hou's study, among 55.56% of isolates that produced biofilm in phenotypic test, 11.11% contained the icaA gene (26), but the other genes has not been investigated. In this study, methicillin resistant isolates harbored higher rate of icaADBC genes compared to MSSA, but no significant difference was confirmed, similar to two other studies (27,28). Moreover, Smith determined no significant relation between susceptibility to methicillin and biofilm formation (29).…”
Section: Discussionsupporting
confidence: 85%
“…Addition of sugar helps in biofilm formation. 16,17 This was also reported by studies conducted by Mathur et al 13 and Bose et al 18 Tube method detected 49% isolates as biofilm producers and 51% as non-biofilm producers. By this method, three isolates were found to be false positive and 19 were false negative.…”
Section: Discussionsupporting
confidence: 57%
“…In accordance with the preceding studies, TM cannot be suggested as general screening test to identify biofilm producing isolates. 8,13 In another study, Ruzicka et al 19 noted that out of 147 isolates of S. epidermidis, TM detected biofilm formation in 79 (53.7%) and CRA detected in 64 (43.5%) isolates. They showed that TM is better for biofilm detection than CRA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations